Characteristic trajectories of ecosystem services in mountains - Locatelli, Bruno; Lavorel, S.; Sloan, S.; Tappeiner, U.; Geneletti, D. (Wiley, 2017)
Intensification of land use and management over recent decades has resulted in trade‐offs between food or timber production and other ecosystem services (ES). Despite an increase in scholarly publications on ES, the temporal aspects of ES trade‐offs have largely been neglected to date. Here we explore how past and future land‐use trajectories (pathways of change) influence ES over time, using mountain landscapes as a model. Based on a synthesis of 51 cases of temporal changes in ES within mountain landscapes, we analyze how changes in land‐use intensity influence the supply of ten key services and we describe six typical examples (archetypes) of ES change. Our analysis reveals that land‐use intensity is an important factor shaping these archetypes. Land‐use intensification often degrades ES (eg recreation and water regulation), with the exception of services targeted by intensification (food or timber) and with differences between forest and agricultural intensification. Service degradation following intensification is not always reversed by reductions in land‐use intensity (termed “extensification”).